Extraction, Characterization, and Molecular Weight Determination of Senna tora (L.) Seed Polysaccharide - Harshal A. Pawar; K. G. Lalitha (International Journal of Biomaterials)
The objective of the present work was extraction of polysaccharide from Senna tora L. seed and its characterization as a pharmaceutical excipient. Polysaccharide extraction was based on mechanical separation of the endosperm of seeds of Senna tora, water dissolution, centrifugation, and precipitation with acetone. Standard procedures were used to study the viscosity, micromeritic properties, and microbial bioburden. Accelerated stability study was carried out on isolated polysaccharide for six months at 40°C/75 RH as per ICH guidelines. The gum obtained from S. tora seeds was an amorphous free flowing odourless powder with dull brown colour (yield = 35% w/w). The bulk density, tapped density, and angle of repose data reveal that S. tora gum possesses good flow property. The intrinsic viscosity obtained was 1.568 dL/g. The average molecular weight of purified S. tora gum was found to be 198 kDa by intrinsic viscosity method. The results indicated that viscosity of gum solution increases with increase in temperature. FTIR study revealed the absence of degradation or decomposition of polysaccharide at accelerated stability conditions for six months. It has been concluded that extracted polysaccharide can be used as pharmaceutical excipient in terms of flow behavior, microbial properties, and stability.